O Núcleo de Apoio à Saúde da Família sob a ótica de usuários e profissionais da Estratégia Saúde da Família - Oliveira, Dayana Kelly Silva [UNIFESP] (2014)
Purpose: To analyze the perception about the working process of the Núcleo de Apoio à Saúde da Família (NASF) in perspective of users and professionals of ESF on Basic Family Health Units in the Zona Leste of São Paulo - Brazil. Methods: A qualitative research conducted through semi-structured interviews and focus as instruments of data collection group was performed. Interviews were conducted with 18 ESF professionals and the focus group developed with six users of the same service. Interviews and focus groups were transcribed and analyzed according to the content analysis technique. Four categories were evident from the analysis of the professionals: knowledge of health professionals on the NASF proposal; NASF working process on ESF; relationship between ESF practices and NASF; and difficulties, challenges and expectations. Each category was divided into three subcategories to facilitate understanding. For the group of users, the analysis allowed to define two categories: user relationship with the ESF and user relationship with the health network. Results: It was observed in the study that the NASF has several limitations and obstacles to be overcome, such as number of teams NASF versus ESF teams, health networks insufficient and inefficient, large pent-up demand, not NASF identification by population, disability in health education and professional high turnover. These limitations, therefore, can lead to misunderstanding of the proposal by the ESF and NASF; conducting specialized care by the NASF; weakened the relationship between NASF and ESF; the overhead of all professionals involved; among others. Conclusion: Given the breadth of the subject, highlights the need for further studies addressing other aspects and perceptions related to NASF working process to contribute to expand the resolution and realization of wholeness in Primary Health Care.